Case report: Recurring and treatment-resistant depression in acquired hepatocerebral degeneration due to a congenital portosystemic shunt - Tamura, Takehiro; Takagi, Shunsuke; Hayakawa, Akane; Oyama, Jun; Fujino, Junya; Shiwaku, Hiroki; Takahashi, Hidehiko; Sugihara, Genichi (Frontiers in Psychiatry, 2024)
Introduction: Acquired hepatocerebral degeneration (AHD) is a neurological condition associated with cerebral manganese (Mn) accumulation caused by portosystemic shunts (PSS), usually because of advanced liver disease. AHD is diagnosed by the identification of T1-weighted brain magnetic resonance imaging (MRI) hyperintensities coupled with the presence of PSS and neurological symptoms. Clinical presentations primarily involve motor dysfunction and cognitive impairment. As a result of the frequently concurrent hepatic encephalopathy, the psychiatric symptoms of AHD alone remain unclear. This report is the first documentation of unique psychiatric symptoms of AHD due to a congenital PSS (CPSS) and suggests the efficacy of shunt embolization in achieving sustained remission of psychiatric symptoms in such cases. Methods: A 57-year-old Japanese woman presented with recurrent severe depression, pain, and somatosensory hallucinations, along with fluctuating motor dysfunction, including parkinsonism, and cognitive impairments. Psychiatric interventions, including antidepressants, antipsychotics or electroconvulsive therapy, had limited efficacy or did not prevent relapse. Results: T1-weighted MRI showed bilateral hyperintensity in the globus pallidus. No history of Mn exposure or metabolic abnormalities, including copper, was identified. Furthermore, no evidence of liver dysfunction or hyperammonemia was found. Eventually, a gastrorenal shunt was observed on contrast-enhanced abdominal computed tomography. The diagnosis of AHD due to CPSS was made based on the clinical manifestations and abnormal imaging findings. Shunt embolization was performed, which prevented the relapse of psychiatric symptoms and substantially reduced the T1-weighted MRI hyperintensities. Conclusions: This case highlights the potential involvement of AHD in adult-onset psychiatric symptoms, even in the absence of liver disease. Furthermore, this case underscores the efficacy of shunt embolization in treating the psychiatric symptoms of AHD due to CPSS.